The millennial consumer's perception of digital messages from the banking sector during the pandemic - de la Vega, Andrea (2022)
During the pandemic, brands have seen the need to create messages with greater authenticity in order to become closer and be more relevant to the consumer. Thus, advertisements on digital platforms during the COVID-19 crisis came to modify their essence and structure, telling stories that involved the subject more and making him the protagonist of the message. Some authors have catalogued this restructuring of the advertising discourse during the crisis as Advertcrisis: a creative line that uses the crisis itself to elaborate messages that promote products and services. There are several categories that have used this formula -such as the banking category-, which used the crisis as a creative line to develop its discourse. For this reason, many messages focused on highlighting concepts such as union, progress or improvement. The objective of this study was to analyze, through in-depth interviews, the perception of men and women about the digital messages that some brands of the banking category developed during the first months of the pandemic. It has been observed how the participants of this research have had a negative perception of these many of the virtual strategies, since these have only been limited to emit empty emotional messages, unrelated to the real problems they were going through.